PENGARUH PENGETAHUAN INVESTASI DAN MOTIVASI INVESTASI TERHADAP MINAT MAHASISWA BERINVESTASI CRYPTOCURRENCY (STUDI EMPIRIS MAHASISWA FEBIS JURUSAN AKUTANSI UNIVERSITAS PATTIMURA) - Kaya, Almendo; Sososutiksno, Christina; Usmany, Alfin Ernest Marthen (Jurnal Akuntansi Kompetif, 2025)
The advancement of digital technology today has changed society's perspective on investment, especially with the emergence of cryptocurrency which has begun to be favored as a new investment alternative. This is interesting to study because many young people are starting to look at digital investments, but not many understand what factors actually drive them to invest. This study aims to empirically examine the influence of investment knowledge and investment motivation on students' interest in investing in cryptocurrency. This research uses quantitative research methods. The sampling technique in this study uses purposive sampling technique. The population in this study is students of Pattimura University, while the sample in this study is students of the Faculty of Economics and Business majoring in accounting class of 2020. Data were analyzed using IBM SPSS 27. The results of this study show that investment knowledge has a negative effect on investment interest so the hypothesis is rejected, investment motivation has a positive effect on investment interest, so the hypothesis is accepted.